Trust and incentives for transboundary groundwater cooperation. (September 2021) - Penny, Gopal; Müller-Itten, Michèle; De Los Cobos, Gabriel; Mullen, Connor; Müller, Marc F.
Highlights: We apply game theory to explore key economic and hydrological aspects of transboundary aquifer cooperation. Cooperative behavior depends on trust and the marginal benefit of pumping. Both water scarcity and groundwater connectivity increase risk and limit pathways for cooperation. Abstract: International transboundary aquifers provide important water supplies to over 150 countries. Long-term sustainability of these aquifers requires transboundary cooperation and yet only a select few (1%) transboundary aquifers are regulated by a treaty. To better understand the incentives that allow treaties to emerge, we develop a two-player game theoretic model that couples groundwater behavior and economic incentives to represent the social dilemma of transboundary aquifer cooperation. The game incorporates economic incentives and hydrogeological features and highlights the importance of trust to evaluate the benefits and risks of a treaty. We demonstrate the ability of the game to reproduce key features of cooperation in the Genevese aquifer, which is governed by the longest-running and most collaborative transboundary aquifer treaty on record. We analyze the comparative statics of the game to explore the role of groundwater connectivity, alternative water supply, water demand, and trust on the emergence of transboundary treaties. The solution space highlights how economic incentives for cooperation are greatest when the value of water is commensurate with the cost of groundwater abstraction. Cooperation requires high trust in situations characterized by water abundance or scarcity. The model results further indicate how two different types of agreements are likely to emerge. Treaties that limit how much is being pumped have greater potential when countries have access to an alternative water source, whereas treaties that restrict where the aquifer is being exploited have greater potential in water-scarce regions with emerging concerns over groundwater depletion. In addition to helping explain the emergence of existing treaties, this framework offers potential to identify aquifers that may be amenable to cooperation.